Answer:
A. 4x⁴ - 4x³ - 16x² - 16x
B. 4x⁴ - 4x³ - 16x² + 16x
Step-by-step explanation:
If you want to find the product of 2 binomial (or even polynomial) expressions, you simply need to multiply every term in one expression by every term in the other:
A.
(4x² - 4x)(x² - 4) = 4x²(x²) + 4x²(-4) - 4x(x²) - 4x(4)
= 4x⁴ - 16x² - 4x³ - 16x
= 4x⁴ - 4x³ - 16x² - 16x
[tex]\left[\begin{array}{ccc}*&4x^{2}&-4x\\x^{2}&4x^{4}&-4x^{3}\\-4&-16x^{2}&-16x\end{array}\right][/tex]
B.
(x² + x - 2)(4x² - 8x) = x²(4x²) + x(4x²) - 2(4x²) + x²(-8x) + x(-8x) - 2(-8x)
= 4x⁴ + 4x³ - 8x² - 8x³ - 8x² + 16x
= 4x⁴ - 4x³ - 16x² + 16x
[tex]\left[\begin{array}{cccc}*&x^{2}&x&-2\\4x^{2}&4x^{4}&4x^{3}&-8x^{2}\\-4x&-4x^{3}&-4x^{2}&8x\end{array}\right][/tex]
Descending order simply means the powers must be largest first and smallest last.